(untitled) ("Journal "U". Economy. Management. Finance.", 2024)
Environmental risk currently represents the potential for a negative impact on the environment due to anthropogenic or natural processes. Environmental risks can include a wide range of events, from industrial accidents to natural disasters and climate change. In the modern world, where organizations are constantly competing in the production of high-quality and innovative products, ecology is becoming one of the key areas of development. Living conditions on our planet have a direct impact on the health of people working in enterprises, including both employees and managers. Their well-being is directly related to the efficiency of companies. However, industrial facilities are often located in large cities, especially heavy industry enterprises that emit pollutants into the atmosphere, as well as various harmful industries. This makes the task of preserving public health and protecting the environment both difficult and urgent. Research in the field of ecology and nature conservation currently remains extremely important.